Peripartum cardiomyopathy - Cárdenas Casallas, Laura Daniela; Rueda Monsalbe, Amanecer; Castañeda Martínez, Diego Andrés; Pinilla Romero, Erika Eliana (Subcomité editorial y de evaluación de obras de la Facultad de Ciencias de la Salud Editora Revista Dra. Bibiana Matilde Bernal Gómez, 2020)
Peripartum cardiomyopathy (PPCM) is a rare, dilated heart disease of unknown origin and potentially fatal, for which various hypotheses have been postulated to explain its genesis, among which are viral myocarditis, immune response and own hemodynamic stress of pregnancy, among others. It usually begins with clinical manifestations of heart failure, which appear during the last month of pregnancy or the five months postpartum. As for the diagnosis, it is considered difficult to carry out, due to the number of diseases that have the same clinical characteristics and considering that other entities can overcome it, for this reason it is considered a diagnosis of exclusion, that is why , its diagnostic approach implies to achieve a complete history, whose findings are supported by paraclinical tests that allow to rule out other possible etiologies that may explain the affectation to the health of the pregnant woman. Another aspect of particular importance encompasses therapeutic considerations, for which it is necessary to keep in mind regimens that acomplish the best quality of life for both pregnant and postpartum women as well as for the product of pregnancy. The objective of this review article is to present updated information on this pathology, including aspects such as its epidemiology, risk factors, clinical manifestations, diagnostic approach, and pharmacological and life-support therapeutic measures.